2011
DOI: 10.1158/1541-7786.mcr-10-0325
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein HuR Promotes Glioma Growth and Treatment Resistance

Abstract: Posttranscriptional regulation is a critical control point for the expression of genes that promote or retard tumor growth. We previously found that the mRNA binding protein, ELAV 1 (HuR), is upregulated in primary brain tumors and stabilizes growth factor mRNAs such as VEGF and IL-8. To better understand the role of HuR in brain tumor growth, we altered levels of HuR in glioma cells by shRNA or ectopic expression and measured tumor cell phenotype using in vitro and in vivo models. In HuR-silenced cells, we fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 31 publications
11
125
0
Order By: Relevance
“…BCL2 mRNA bears an AU-rich 3′ UTR and was reported to be a target of an RNA-binding protein, ELAV-like protein 1 (HuR). 25,26 Consistent with this report, HuR bound to BCL2 3′ UTR-4 ( Figure 2b). We further divided 3′ UTR-1 into four overlapping fragments (3′ UTR-A, -B, -C, and -D) and found that Tra2β predominantly bound to the region within 3′ UTR-B (nt 1294-1541; Figure 2c Figure 2e, the rate of decay for BCL2 mRNA in Tra2β siRNA-treated cells in the presence of actinomycin D (t 1/2 = 2.1 ± 0.3 h) was faster than that of control siRNA-treated cells (t 1/2 = 7.5 ± 0.6 h).…”
Section: Resultssupporting
confidence: 89%
“…BCL2 mRNA bears an AU-rich 3′ UTR and was reported to be a target of an RNA-binding protein, ELAV-like protein 1 (HuR). 25,26 Consistent with this report, HuR bound to BCL2 3′ UTR-4 ( Figure 2b). We further divided 3′ UTR-1 into four overlapping fragments (3′ UTR-A, -B, -C, and -D) and found that Tra2β predominantly bound to the region within 3′ UTR-B (nt 1294-1541; Figure 2c Figure 2e, the rate of decay for BCL2 mRNA in Tra2β siRNA-treated cells in the presence of actinomycin D (t 1/2 = 2.1 ± 0.3 h) was faster than that of control siRNA-treated cells (t 1/2 = 7.5 ± 0.6 h).…”
Section: Resultssupporting
confidence: 89%
“…Our previous studies in preclinical pancreatic cancer models (33)(34)(35)(36)(37)(38), as well as studies by others (17,19,20,24,(39)(40)(41), provided the rationale for investigating HuR inhibition in ovarian tumors We first established that suppression of HuR expression reduces proliferation, anchorage-independent growth, and invasion of ovarian cancer cells in vitro. We further demonstrate HuR inhibitionmediated reduction in tumor growth rate, delay in ascites development, and extension of lifespan by nearly 1.5-fold in two different ovarian cancer mouse models, a xenograft model and an orthotopic model in which mice bear tumors throughout the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HuR in posttranscriptional regulation of multiple genes that promote survival of ovarian tumor cells provides an opportunity to develop an alternative strategy that targets multiple core signaling pathways at once. Indeed, proof-of-concept studies using HuR knockout mice and intracranial injection of mice with genetically silenced HuR primary glioblastoma cells have shown a reduction in colon tumor and glioblastoma growth, respectively (19,20). One approach to inhibit HuR is through targeted delivery of functional siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports established the neuroprotective effect of Bcl-2 in neurons. [61][62][63] HuR has also been linked to the activation of prosurvival Bcl-2 family members 56,64,65 through the regulation of their turnover and translation, 56,[66][67][68] In HT-22 cells, HuR maintains Bcl2 mRNA stability and translation at a constant rate to buffer its requirement during assault and preserve mitochondrial homeostasis.…”
Section: Discussionmentioning
confidence: 99%